2009
DOI: 10.1158/1055-9965.epi-09-0925
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Filter–based Assays as Proxies for Toxicant Exposure and Smoking Behavior—A Literature Review

Abstract: Background: Cigarettes are being marketed with filters that differ in composition and design. The filters have different toxicant trapping efficiencies, and smoking stains reflect variations in smoking behavior. Presented herein are the results of a structured literature review that was done to identify cigarette filter-based assays that may serve as proxies for mouth-level exposure and assessing smoking methods. Methods: A search of the published scientific literature and internal tobacco company documents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 67 publications
(72 reference statements)
0
23
0
1
Order By: Relevance
“…Humans smoke their cigarettes differently from a standard smoking machine (Borgerding & Klus 2005); thus, smoking topography (i.e., total puff volume, puff count, puff velocity, duration of puff and puff interval) would be a more appropriate method to estimate any possible change in smoking behaviour (Pauly et al 2009;Mariner & Shepperd 2011).…”
Section: Effect Of the Band On Mainstream Smoke Yieldsmentioning
confidence: 99%
“…Humans smoke their cigarettes differently from a standard smoking machine (Borgerding & Klus 2005); thus, smoking topography (i.e., total puff volume, puff count, puff velocity, duration of puff and puff interval) would be a more appropriate method to estimate any possible change in smoking behaviour (Pauly et al 2009;Mariner & Shepperd 2011).…”
Section: Effect Of the Band On Mainstream Smoke Yieldsmentioning
confidence: 99%
“…A literature review conducted by PAULY et al (6) highlighted the fact that all the research identified using filter based assays was performed exclusively using cigarettes with cellulose acetate filters. There were no published studies which incorporated RRPs or other smoking articles (e.g., electrically heated cigarettes).…”
Section: Resumementioning
confidence: 99%
“…Nevertheless, it is possible that the artificial feel of smoking topography devices alters puffing topography and/or smoking topography. To determine more accurately MLE to mainstream cigarette smoke in natural settings, the analysis of spent cigarette butts has been described as the least invasive of the methods mentioned above (9)(10)(11)(12). The basic principle is that the amount of "tar" and nicotine that emerge from the filter are proportional to the amounts trapped in the part-filter section.…”
Section: Introductionmentioning
confidence: 99%